Sequential Mediation Analysis on The Relationship Between Servant Leadership And Affective Commitment to Change: Evidence from Indonesia - Reni Rosari; Heni Ardianto; Vania Olivine Danarilia (Asian Academy of Management Journal, 2025)
One of the most significant challenges facing leaders today is the need to position and enable organisations and people to adapt to an increasingly dynamic and demanding environment. This study examined and analysed the role of servant leadership in affective commitment to change in the higher education sector using a sequential mediation model of conscientiousness personality and psychological ownership. The data were collected online from 293 Indonesian lecturers. Data analysis was performed using a structural equation model using SmartPLS software. The results confirmed that implementing servant leadership encourages positive values in social learning principles in higher education, which can improve conscientiousness and psychological ownership. Conscientiousness and psychological ownership support social learning, according to the principle of servant leadership, to encourage a robust affective commitment to change in a higher education environment. Conscientiousness and psychological ownership are sequential mediators that influence affective commitment to change. This study is unique in that it highlights the conscious personality factor and psychological aspects as sequential mediation on the relationship between servant leadership and affective commitment to change in the higher education sector, as well as the fact that although all hypotheses are supported, this sequential mediation mechanism is the first such study.